Investigation into the supply-demand relationship of carbon sequestration in the yellow river basin using the optimal parameter geographical detector model - Heng Zhao; Yingying Gai; Fuqiang Wang; Lanbo Cui; Yutian Du; Heng Wang; Lei Tang; Huan Yang (Scientific Reports)
Abstract The carbon cycle is crucial for ecosystem regulation. Carbon sequestration services (CSS) stabilize and fix CO2 in ecosystems over the long term, which is crucial for mitigating global climate change and promoting sustainable development. This study quantified the supply and demand of CSS in the Yellow River Basin from 2001 to 2021 using the InVEST model and urban metabolism approach. Additionally, the advanced Optimal Parameter Geodetector (OPGD) model was employed to explore the carbon sequestration service demand-supply relationship (CSSDR) and its driving mechanisms. Results showed: (1) CSS supply increased to varying degrees, while demand fluctuated upwards, with higher demand in downstream and lower in upstream areas. (2) Spatial CSSDR imbalance was evident at the grid scale, with significant regional differences and a declining CSS supply-demand index at the provincial level. (3) CSS supply was mainly influenced by natural factors, while demand was driven by human activities and socio-economic development. Increasing population and GDP densities disrupted the balance, becoming key determinants of CSSDR. (4) Interactions between drivers exhibited dual-factor enhancement and non-linear amplification, with population density showing the most significant correlations (all q-values > 0.67). These findings underpin improved environmental protection and sustainable development strategies in the region.